Common Bean: A Legume Model on the Rise for Unraveling Responses and Adaptations to Iron, Zinc, and Phosphate Deficiencies - Castro-Guerrero, Norma A.; Isidra-Arellano, Mariel C.; Mendoza-Cozatl, David G.; Valdés-López, Oswaldo (Frontiers in Plant Science, 2016)
Common bean (Phaseolus vulgaris) was domesticated ~8000 years ago in the Americas and today is a staple food worldwide. Besides caloric intake, common bean is also an important source of protein and micronutrients and it is widely appreciated in developing countries for their affordability (compared to animal protein) and its long storage life. As a legume, common bean also has the economic and environmental benefit of associating with nitrogen-fixing bacteria, thus reducing the use of synthetic fertilizers, which is key for sustainable agriculture. Despite significant advances in the plant nutrition field, the mechanisms underlying the adaptation of common bean to low nutrient input remains largely unknown. The recent release of the common bean genome offers, for the first time, the possibility of applying techniques and approaches that have been exclusive to model plants to study the adaptive responses of common bean to challenging environments. In this review, we discuss the hallmarks of common bean domestication and subsequent distribution around the globe. We also discuss recent advances in phosphate, iron, and zinc homeostasis, as these nutrients often limit plant growth, development and yield. In addition, iron and zinc are major targets of crop biofortification to improve human nutrition. Developing common bean varieties able to thrive under nutrient limiting conditions will have a major impact on human nutrition, particularly in countries where dry beans are the main source of carbohydrates, protein and minerals.